Multi-omics analysis revealed the differences in lipid metabolism of the gut between adult and juvenile yellowfin tuna (Thunnus albacares) - Zou, Ying; Zhang, Yanjie; Wu, Di; Lu, Zhiyuan; Xiao, Juan; Huang, Hai; Fu, Qiongyao; Guo, Zhiqiang (Frontiers in Microbiology, 2024)
Tuna has a cost-effective energy supply to support the regional endothermic and high-speed swimming performance. The gut symbiotic microbiotas and their metabolites play essential roles in tuna's diet digestion, absorption, and energy acquirement, which are often highly related to the ontogenetic development of tuna.We compared gut microbial compositions and metabolites, as well as mRNA expression of the intestine between juvenile and adult yellowfin tuna using 16S rRNA sequencing, metabolomic and transcriptomic, respectively.The results revealed that adults had a significantly higher microbial diversity and abundance of Acinetobacter than juveniles. Regarding the gutderived metabolites, we found that fatty acids, especially glycerophospholipid and sphingolipid were significantly enriched in adults than juveniles. Moreover, the SCFAs short chain fatty acids (butyrate and isobutyrate) contents had significantly increasing higher levels in adults than in juveniles. To find the relationship between gut microbiotas and host physiologyphycology, intestinal transcriptome analysis demonstrated that the enriched pathways of differential expression genes (DEGs) in adult tuna were the lipid metabolism pathway, including "fat digestion and absorption", "cholesterol metabolism", "steroid hormone biosynthesis", "glycerolipid metabolism", and "glycerophospholipid metabolism". Whereas, protein digestion and absorption and pancreatic secretion pathways were significantly enriched in the juveniles. The conjoint analysis indicated that the enriched pathways of both differential metabolites (DMs) and DEGs were remarkably related to the regulation of glycerophospholipids metabolism in adult tunas. This study highlights the role of gut microbiotas in fish nutrition metabolism. These findings provide new insights into the view of ontogenetic shifts of gut microbiotas and their metabolites on host health and gut function in endothermic and high-speed swimming marine fish species.